Targeting Lysosomal Dysfunction and Oxidative Stress in Age-Related Macular Degeneration - Ana S. Falcão; Margarida L. Pedro; Sandra Tenreiro; Miguel C. Seabra (Antioxidants)
Age-related macular degeneration (AMD) is the leading cause of vision loss in the Western world, and it currently lacks effective therapy. It is believed that AMD initiates in the aged retinal pigment epithelium (RPE), which presents lysosomal dysfunction and oxidative stress (OxS) that ultimately leads to RPE damage and AMD progression. AMD is a complex pathology, so multitarget treatments are required to act on different pathways, presenting several challenges. In this review, we discuss the current knowledge on the pathogenesis of this disease, focusing mainly on lysosomal dysfunction and OxS. Because transcription factors regulate homeostasis, the transcription factor EB (TFEB), which controls lysosomal function and biogenesis, and the nuclear factor erythroid 2-related factor 2 (NRF2), which manages OxS, have been proposed as promising targets for disease intervention. Finally, we discuss the interplay of these pathways for a potential synergistic effect on AMD-targeted therapies, as they could change the course of today’s available treatments for AMD.